1996
DOI: 10.1155/1996/743570
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Routine Enteric Pathogens in Hospitalized Patients: A Canadian Perspective

Abstract: K GOUGH, M ALFA, G HARDING. Evaluation of routine enteric pathogens in hospitalized patients: A Canadian perspective. Can J Infect Dis 1996;7(3):197-202. Diarrhea is a frequently encountered problem in hospitalized patients. Since nosocomial spread of routine enteric pathogens such as Salmonella species, Shigella species, Campylobacter species and Escherichia coli O:157 H:7 seldom occurs, testing for these organisms in patients hospitalized for longer than three days has been questioned. The goal of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…This retrospective evaluation of FilmArray GI panel tests performed on hospitalized adult patients admitted for Ͼ72 h in an academic tertiary-care hospital demonstrates that there is low yield of new positive results (4.8% overall and 3.0% after exclusion of chronic norovirus shedders and potential false positives) in this hospitalized population, similar to published literature for conventional stool cultures and exams for protozoa (3)(4)(5)(6), even though the FilmArray GI panel detects additional pathogens not routinely detected by conventional methods. No significant difference in positivity rates between immunocompromised and immunocompetent patients was seen in this study, although it was underpowered for this comparison.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This retrospective evaluation of FilmArray GI panel tests performed on hospitalized adult patients admitted for Ͼ72 h in an academic tertiary-care hospital demonstrates that there is low yield of new positive results (4.8% overall and 3.0% after exclusion of chronic norovirus shedders and potential false positives) in this hospitalized population, similar to published literature for conventional stool cultures and exams for protozoa (3)(4)(5)(6), even though the FilmArray GI panel detects additional pathogens not routinely detected by conventional methods. No significant difference in positivity rates between immunocompromised and immunocompetent patients was seen in this study, although it was underpowered for this comparison.…”
Section: Discussionsupporting
confidence: 66%
“…Due to the sensitivity of the assay, it has taken the place of conventional stool cultures and parasite exams for protozoa in some institutions. Historically, conventional stool microbiology tests are not performed after a patient has been admitted for more than 3 days, as multiple studies have shown that the yield in hospitalized patients is exceptionally low (Ͻ1.5%) (3)(4)(5)(6). Given that FilmArray GI panel tests for bacterial, viral, and protozoal pathogens not routinely detected by conventional microbiological assays, it is not known if this same standard should be applied to this test.…”
mentioning
confidence: 99%
“…Of the 1·9%, 39% were isolated from patients aged 0–4 years, whereas only 20% of the Salmonella spp.-positive outpatient specimens were isolated in the same age group. It has been reported that the majority of enteric pathogens isolated from inpatients in a hospital represent patients who had been hospitalized for <2 days, suggesting the infection was a result of exposure to the pathogen prior to being admitted to the hospital [24]. The number of days hospitalized prior to submitting a stool sample was not collected in this study but would help inform our interpretation of exposure source, especially for inpatients aged 0–4 years, in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Because of the variety of organisms, it is difficult and expensive for clinical laboratories to do a complete etiological examination of diarrheal stool specimens. Some investigators, mostly studying adult populations, have recently questioned the appropriateness of performing a complete etiological examination on stool specimens for diarrheal diseases (13)(14)(15)(16)(17)(18). The few published reports on stool testing in the paediatric population have either not differentiated CAD from NAD (19)(20)(21), or have excluded viral testing or screening for ova and parasites (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%